Treatment Effect of Bumetanide in Children With Autism Spectrum Disorder: A Systematic Review and Meta-Analysis - Wang, Tiantian; Shan, Ling; Miao, Chunyue; Xu, Zhida; Jia, Feiyong (Frontiers in Psychiatry, 2021)
Background: The therapeutic effect of bumetanide on autism spectrum disorder (ASD) seems to be controversial. To obtain better evidence on the efficacy of bumetanide, a systematic review and meta-analysis were performed. Methods: Randomized, placebo-controlled trials (RCTs) of bumetanide treatment in children with ASD were identified through systematic review from database inception to January 17, 2021. Subsequently, a meta-analysis was carried out to examine the effect of bumetanide on the severity of symptoms of ASD as assessed by the Childhood Autism Rating Scale (CARS) and Social Responsive Scale (SRS); core symptoms according to criteria of the Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 of the American Psychiatric Association [social affect (SA), restricted, repetitive patterns of behavior, interests, or activities (RRB) and sensory symptoms]; and the therapeutic effect as assessed by Clinical Global Impressions-Efficacy (CGI-E). Results: In total, six RCTs involving 496 participants with ASD were identified in our study. The results showed that bumetanide could significantly improve the severity of the ASD symptoms measured by CARS and SRS. There was also evidence that bumetanide had positive effect on the core symptoms of ASD such as the SA and RRB, but there was no statistically significant effect on sensory symptoms. A significant positive effect on CGI-E scores in ASD patients was also observed. Conclusion: Our meta-analysis provided some support that bumetanide could improve the symptoms of children with ASD. However, additional large-scale longitudinal studies that provide clearer information and better control for confounding factors are needed to confirm our findings.